2021
DOI: 10.3201/eid2702.191795
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNA Profiling of Plasmodium falciparum Biomass and Association with Severity of Malaria Disease

Abstract: Severe malaria (SM) is a major public health problem in malaria-endemic countries. Sequestration of Plasmodium falciparum –infected erythrocytes in vital organs and the associated inflammation leads to organ dysfunction. MicroRNAs (miRNAs), which are rapidly released from damaged tissues into the host fluids, constitute a promising biomarker for the prognosis of SM. We applied next-generation sequencing to evaluate the differential expression of miRNAs in SM and in uncomplicated malaria … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…TaqMan-advanced quantitative reverse transcription PCR (RT-qPCR) assays were used to measure miRNA levels using 50 μl of plasma (supplementary materials). 4 The selection of miRNAs was based on published reports (supplementary materials; Figure S2). Cycle threshold values were <24 in all samples, with a coefficient of variance < 6% for the exogenous control (cel-miR-39-3p) amplified by RT-qPCR, indicative of a successful cDNA preparation.…”
Section: Plasma Levels Of Hsa-mir-3158-3p Microrna On Admission Correlate With Mri Findings and Predict Outcome In Cerebral Malariamentioning
confidence: 99%
“…TaqMan-advanced quantitative reverse transcription PCR (RT-qPCR) assays were used to measure miRNA levels using 50 μl of plasma (supplementary materials). 4 The selection of miRNAs was based on published reports (supplementary materials; Figure S2). Cycle threshold values were <24 in all samples, with a coefficient of variance < 6% for the exogenous control (cel-miR-39-3p) amplified by RT-qPCR, indicative of a successful cDNA preparation.…”
Section: Plasma Levels Of Hsa-mir-3158-3p Microrna On Admission Correlate With Mri Findings and Predict Outcome In Cerebral Malariamentioning
confidence: 99%
“…Thus, determining direct or indirect markers of early and still progressing organ dysfunction in the context of SM could revolutionize its clinical management. A recent, large-scale study using a combination of in vitro models and plasma samples from Mozambican children infected with Pf and diagnosed with SM or UM demonstrated for the first time the association between both hsa-miR-3158-3p and hsa-miR-4497 with SM, its complications, and Pf biomass ( Figure 1c ) ( Gupta et al., 2021a ). These findings suggest that although unable to produce miRNAs ( Xue et al., 2008 ), Plasmodium may manipulate the production of host miRNAs.…”
Section: And Seek: the Symptomatic Erythrocytic Phasementioning
confidence: 98%
“…Higher levels of miR-3158–3p were measured in Mozambican children who had acidosis or ARDS compared to UM children. In contrast, miR-4497 was associated with severe anemia and ARDS ( Figure 1c ) ( Gupta et al., 2021a ). A review suggested that miR-210; miR-125b and miR-181b; as well as miR 17–92 and miR-24 could be promising miRNA-based biomarkers of acidosis, ARDS and renal failure, respectively ( Figure 1c ) ( Chamnanchanunt et al., 2017 ).…”
Section: And Seek: the Symptomatic Erythrocytic Phasementioning
confidence: 99%
See 2 more Smart Citations